Archaeology “Under the flag of Lithuanian SSR Department of History” - Luchtanas, Aleksiejus (Archaeologia Lituana, 2010)
The development of archaeology in Soviet Lithuania has not yet received a more extensive study. Vilnius University (VU) was the only higher education institution that prepared archaeology specialists and it ceased to do so after the closing of the Archaeology and Ethnography Department in 1966. In 1973 Lithuanian SSR Department of History established an Archaeology-Museology speciality. Even with limited possibilities, 120 archaeologists-museologists graduated until the reopening of the Archaeology Department in 1990. During the archaeological fieldwork practise for students intended in the curriculum, the Lithuanian SSR Department of History used to organise scientific expeditions. Some were independent investigations; others were conducted with the Lithuanian SSR Institute of History of the Academy of Sciences. The focus was mainly on the Užnemunė hillforts and since 1972 on large feudal centres in Eastern Lithuania. Maišiagala and Narkūnai hillforts were excavated. In 1979 Kernavė archaeological site became the main VU archaeological research base. After ten years of VU excavation seasons, State Archaeology and History Reserve was founded in 1989, and in 2004 the Kernavė archaeological site was added to the UNESCO list of World Heritage Objects. Archaeology students that went on Kernavė expeditions were introduced to fieldwork methods and performed natural science and chemical-physical tests on archaeological material. Foreign students also participated in the Kernavė expeditions. From 1966 to 1990 few of the VU archaeologists (1 to 4 people were working) successfully defended one habilitation and one doctoral dissertation, published several important monographs and scientific articles, and actively participated in scientific conferences. It was only after the reestablishment of Independence in 1990 that it was possible to reopen the Archaeology Department in Vilnius University.